CONCEPTUAL APPROACHES TO THE DEVELOPMENT OF THE AGRICULTURAL SECTOR IN TERMS OF THE CLOSED-CYCLE ECONOMY - Natalia A. Prodanova; Alexander A. Savin; Sergey N. Kosnikov; Ilya V. Sorgutov (Siberian Journal of Life Sciences and Agriculture, 2021)
The current stage of development of the agricultural industry is characterized by high rates of automation of production processes. In this regard, the problem of rationalizing the process of distributing agricultural resources and organizing the production chain with added value is becoming more acute. An effective solution to this problem can be a closed-cycle economy model. This model can contribute to the rational use of resources, reduce production losses, and, as a result, improve the quality of products and their volumes. It is necessary to develop a general plan for the implementation of the main postulates of the closed-cycle economy in agriculture, gradually implement the circular economy strategy and include new industrial circular economy in the process of modernization of a particular branch of agriculture. In some areas of agriculture, a cycle of production systems should be established as soon as possible. With the basic implementation of new industrial technologies and industrial development, as well as the stability of the reserves of social resources, it is necessary to steadily increase the new cycle of industrialization in agriculture.